Implementation of cervical cancer prevention and screening across five tertiary hospitals in Nepal and its policy implications: A mixed-methods study. - Ganesh Dangal; Rolina Dhital; Yam Prasad Dwa; Sandesh Poudel; Jitendra Pariyar; Kirtipal Subedi (Public Library of Science (PLoS), 2024)
In Nepal, cervical cancer is the most common cancer among women despite the existing policies. This study intends to assess the implementation of cervical cancer prevention and screening through service utilization by women, knowledge and attitude among health professionals, and the perceptions of stakeholders in Nepal. This mixed-methods study was conducted in 2022 across five tertiary hospitals in Kathmandu, Nepal. The quantitative study comprised the health professionals and women attending gynecology outpatient clinics from the selected hospitals. The qualitative study comprised stakeholders including service providers and experts on cervical cancer from selected hospitals, civil societies, and the Ministry of Health and Population. The utilization of screening through pap smear among 657 women across five hospitals was 22.2% and HPV vaccination was 1.5%. The utilization of cervical cancer screening was associated with older age [adjusted odds ratio (AOR) = 1.09, CI: 1.07, 8.19], married (AOR = 3.024, CI: 1.12, 8.19), higher education (AOR = 3.024, CI:1.12, 8.42), oral contraceptives use (AOR = 2.49, CI: 1.36, 4.39), and ever heard of cervical cancer screening (AOR = 13.28, CI: 6.85, 25.73). Among 254 health professionals, the knowledge score was positively associated with them ever having a training [Standardized Beta (β) = 0.20, CI: 0.44, 2.43)] and having outreach activities in their hospital (β = 0.19 CI: 0.89, 9.53) regarding cervical cancer screening. The female as compared to male health professionals (β = 0.16, CI: 0.41, 8.16, P = 0.03) and having a cervical cancer screening guideline as compared to none (β = 0.19 CI: 0.89, 9.53, P = 0.026) were more likely to have a better attitude for screening. The qualitative findings among 23 stakeholders reflected implementation challenges in policy, supply, service delivery, providers, and community. This study showed low utilization of prevention and services by women and implementation gaps on cervical cancer prevention and screening services across five tertiary hospitals in Kathmandu, Nepal. The findings could help designing more focused interventions.